Analysis of the causes and conditions for the formation of surface defects on hot‑rolled products from peritectic steel grades obtained under the conditions OJSC “BSW – Management Company of the Holding “BMC” - A. V. Tereshchenko; N. A. Khodosovskaya; I. B. Odarchenko (Литьë и металлургия, 2021)
OJSC “BSW – Management Company of the Holding “BMC” produces a wide range of carbon, high‑quality, alloyed and high‑carbon steel grades, among which a signifi ant share is peritectic grade steels. Basically, the steel of this group is used to produce rolled products intended for the manufacture of components for the automotive industry. The process of production and casting of these steels is characterized by the greatest instability and is often accompanied by rejects and forced sorting of products. This situation is typical for other metallurgical enterprises. Therefore, the search for technological solutions that ensure an increase in the yield while maintaining the existing productivity of metallurgical units is an urgent aspect of improving the technology of continuous casting of peritectic grade steels. At the same time, the main scientific and technical task is to obtain a stable quality of continuously cast billets, aimed at preventing and eliminating the formation of a number of characteristic defects, primarily cracks on the surface of continuously cast billets and rolled products. The search for methods and technological solutions to improve the quality of products made of peritectic grade steel is the goal of the ongoing research.